A Brotherhood of Britons? Public Schooling, esprit de corps and Colonial Officials in Africa, c.1900–1939. Issue 330 (8th April 2013) - Prior, Christopher
Abstract Historians have tended to suggest that Britain's colonial officials demonstrated an esprit de corps, and that this is testament to the efficacy of public schooling in generating social cohesion. Examining Britain's officials in seven different colonies in sub‐Saharan Africa, this article will argue that differences in working conditions, approaches to work and officials' backgrounds, such as conflicts between officials from 'military' and 'civilian' backgrounds, all caused deep fragmentations in the colonial services. Most significantly, officials were irreconcilably torn between a need for company as a means of maintaining morale, and a desire for freedom from the constraints of colonial society. Living in insular communities driven by gossip and marked by the need to keep up appearances for fear of ostracism from their peers, officials felt unable to experience an 'authentic' Africa and live out the romanticized dreams of individualism that had motivated many to leave for Africa in the first place. This sense of feeling trapped bred resentment towards one's fellow officials. Consequently, public schools were unable to surmount other factors in shaping how officials regarded one other.